Institutionalization-Free Survival and Health Care Costs among Quebec Community-Dwelling Elderly Patients with Dementia. (29th January 2014) - Beland, Sarah-Gabrielle; Pariente, Antoine; Moride, Yola
Abstract : Background. Published data on burden of dementia mainly include patients of third-care facilities. Economic consequences in an outpatient setting remain poorly examined. Objectives. To evaluate institutionalization-free survival and direct health care costs of dementia in the Quebec community-dwelling elderly population. Methods. A retrospective cohort study was conducted using the Quebec administrative claims databases. The cohort included a random sample of patients with treated dementia between January 1, 2000, and December 31, 2009 (n = 37, 138 ). The reference population included elderly patients without dementia matched in age group, gender, and index date. Using a third-party payer perspective, direct costs over 5 years were assessed. Results. Institutionalization-free survival at 5 years was lower in patients with dementia than in elderly without dementia (38.9% and 72.2%, resp.). Over 5 years, difference in mean total direct health care costs per patient was CAD19, 159, distributed into institutionalizations (CAD13, 598), hospitalizations (CAD3, 312), and prescribed medications (CAD2, 320). Costs of medical services were similar (−CAD96). In the first year of followup, cost differentials were mainly attributable to hospitalizations, while in the last year (year 5) they were due to institutionalizations. Conclusion. This study confirms that dementia is an important socioeconomic burden in the community, the nature of which depends on disease progression.